2020
DOI: 10.1038/s41598-020-59937-w
|View full text |Cite
|
Sign up to set email alerts
|

Some Gammaproteobacteria are enriched within CD14+ macrophages from intestinal lamina propria of Crohn’s disease patients versus mucus

Abstract: Crohn's disease causes chronic inflammation in the gastrointestinal tract and its pathogenesis remains unclear. In the intestine of Crohn's disease patients, CD14 + CD11 + CD163 low macrophages contribute to inflammation through the induction of Th17 cells and production of inflammatory cytokines; the CD14 + CD11c + 163 high fraction is anti-inflammatory through the production of IL-10 in normal cases. In this report, the 16S rRNA gene amplicon sequencing method was used to identify bacteria that are specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
11
0
3
Order By: Relevance
“…The reduction in Agathobaculum, which exhibits effects on gut motility regulating ability, could be a contributory factor to the increased severity and frequency of GI dysmotility symptoms in this particular cohort (Kenna et al, 2021), as well as other PwP cohorts (Kaye et al, 2006;Knudsen et al, 2017;Li et al, 2019;Cirstea et al, 2020). On the other hand, Gammaproteobacteria, a pro-inflammatory bacterium that produces endotoxins and is associated with GI disorders such as Crohn's disease (Sekido et al, 2020), and Synergistetes (Synergistia) a bacterium involved in GI infections (Vartoukian et al, 2007), were significantly increased in our PwP cohort. Together, these findings support a significantly altered, pro-inflammatory gut microbiome in PwP.…”
Section: Discussionmentioning
confidence: 91%
“…The reduction in Agathobaculum, which exhibits effects on gut motility regulating ability, could be a contributory factor to the increased severity and frequency of GI dysmotility symptoms in this particular cohort (Kenna et al, 2021), as well as other PwP cohorts (Kaye et al, 2006;Knudsen et al, 2017;Li et al, 2019;Cirstea et al, 2020). On the other hand, Gammaproteobacteria, a pro-inflammatory bacterium that produces endotoxins and is associated with GI disorders such as Crohn's disease (Sekido et al, 2020), and Synergistetes (Synergistia) a bacterium involved in GI infections (Vartoukian et al, 2007), were significantly increased in our PwP cohort. Together, these findings support a significantly altered, pro-inflammatory gut microbiome in PwP.…”
Section: Discussionmentioning
confidence: 91%
“…Elevated levels of Acinetobacter in the setting of IBD has been observed in several studies ( Gophna et al, 2006 ; Lucke et al, 2006 ; Leung et al, 2014 ; Kevans et al, 2015 ; Tang et al, 2015 ; Sjoberg et al, 2017 ; Sekido et al, 2020 ; He et al, 2021 ; Qi et al, 2022 ). Two studies found high abundance of Acinetobacter in pediatric patients with newly diagnosed ulcerative colitis ( Kevans et al, 2015 ; Sjoberg et al, 2017 ); providing potential evidence that Acinetobacter species could be contributing to the onset of intestinal inflammation in genetically susceptible patients.…”
Section: Discussionmentioning
confidence: 81%
“…This study found that Acinetobacter levels significantly correlated with microbial pathways in actively inflamed colitis tissue, suggesting a potential causal relationship between Acinetobacter and intestinal inflammation. Another study identified Acinetobacter in the CD14 + CD11c + CD163low subset macrophages in the lamina propia of ulcerative colitis patients ( Sekido et al, 2020 ), which indicates these microbes were able to bypass the epithelial barrier. In our intestinal organoid model, we found that several A. calcoaceticus strains stimulated pro-inflammatory cytokine expression and suppressed mucin production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, o paciente pode chegar a desenvolver hemorragias, estenoses, perfurações intestinais e até mesmo um carcinoma de colo retal. (SEKIDO et al, 2020;SILVA et al, 2020) Dessa forma, pode-se dizer que esta revisão integrativa de literatura tem como objetivo analisar a influência do sistema imunológico na origem, desenvolvimento e agravamento da Doença de Crohn, enfatizando o papel das células de defesa e seus efeitos na fisiopatologia da comorbidade.…”
Section: Introductionunclassified